DAMPAK SOSIAL DOXING TERHADAP HAK PRIVASI PELAKU KEJAHATAN BERDASARKAN UNDANG-UNDANG NOMOR 27 TAHUN 2022 - Angelita, Valerie; Suradipraja, Varsha Savilla Akbari Candra (Legislatif, 2024)
The rapid development of technology has significantly increased the use of electronic media, particularly social media platforms, which have become integral to daily life. This progress has simplified the collection, management, and storage of personal data, intertwining it with individual activities on these platforms. However, this condition also extends to criminals, whose personal data is often disclosed without adequate protection. This research employs a normative juridical method, involving the analysis of laws, regulations, and legal literature, to explore the necessity of legal protection for the right to privacy, including the personal data of criminals. The study identifies legal gaps in the implementation of personal data protection under Law Number 27 of 2022 and provides recommendations to strengthen policies that uphold privacy as a fundamental human right. The findings emphasize the social consequences of privacy violations, such as stigmatization, social exclusion, and the risk of vigilantism. These outcomes highlight the need for stronger regulations that ensure legal certainty while balancing the rights of victims, offenders, and public interests. Law enforcement plays a critical role in optimizing the application of current regulations by integrating ethical considerations and addressing social impacts. By prioritizing these aspects, this study aims to contribute to the creation of a fairer legal system that respects privacy rights while addressing broader societal concerns. Strengthening these protections is essential to fostering justice and equity in an era where personal data is increasingly vulnerable.